2022
DOI: 10.3390/cells11152375
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-Mediated Silencing Pathways in the Nervous System and Neurological Diseases

Abstract: MicroRNAs (miRNAs) are small noncoding RNAs that play a prominent role in post-transcriptional gene regulation mechanisms in the brain tuning synaptic plasticity, memory formation, and cognitive functions in physiological and pathological conditions [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
(18 reference statements)
0
13
0
Order By: Relevance
“…miRNAs play an inhibitory role at the post-transcriptional level. Its loss or modification was related to an increase in PD-L1 expression, and its deletion via CRISPR Cas9 led to greater stability of PD-L1 mRNA ( Table 1 , Figure 1 ) [ 2 , 49 , 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…miRNAs play an inhibitory role at the post-transcriptional level. Its loss or modification was related to an increase in PD-L1 expression, and its deletion via CRISPR Cas9 led to greater stability of PD-L1 mRNA ( Table 1 , Figure 1 ) [ 2 , 49 , 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some authors hypothesized the role of microRNAs (miR-126-3p, miR-26a-5p, and miR-107) in the diagnosis of arterial hypertension in OSAS patients [ 129 ]. In our opinion, they could be useful for better understanding the etiopathogenetic mechanisms, but they are certainly less relevant from a hypertension diagnostic point of view.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it has been shown that miRNAs influence both various physiological processes during development and tissue homeostasis by regulating the expression of approximately 90% of human genes [14]. Recently miRNAs have been widely studied for their role in various human diseases including tumours [15], haematological diseases [16], cardiovascular diseases [17], and central nervous system diseases [18]. Currently, studies in animal models [19] and bioinformatics [20] analyses have preliminarily demonstrated that alterations in miRNA expression have an impact on key processes in the pathophysiology of SCI.…”
Section: Introductionmentioning
confidence: 99%